Antioxidant ativity of dichloromethane extract from cocoa pod husk (Theobroma cacao L.) - FEBRINA, RESA VERNIA; YAHYA, MUSTANIR; GINTING, BINAWATI; SAIDI, NURDIN (Universitas Syiah Kuala, 2024)
Theobroma cacao L. is a plant that is reported to have strong antioxidant potential. A study was carried out to determine the antioxidant activity of dichloromethane extract of cocoa pod husk using 1,1-diphenyl-2-picrylhydrazyl (DPPH). The cocoa pod husk was macerated using n-hexane, ammonia-dichloromethane, and methanol. The TCD extract of cocoa pod husk showed the lowest IC50 value of 14.59 0.54 ppm based on the DPPH inhibition assay. The dichloromethane extract was isolated by gravity column chromatography with Silica gel G60 as the stationary phase andn-hexane: ethyl acetate as the mobile phase (gradient elution system). Fractions with identical staining patterns were combined into six fractions (TCD 1-TCD 6). The TCD 6 showed the lowest IC50 value of 127.05 0.54 ppm according to the DPPH inhibition assay. Based on the TLC results, TCD 4 was further isolated and four fractions (TCD 4.1 to TCD 4.4) were obtained. The TCD 4.4 had the lowest IC50 value (38.66 0.96 ppm).The TCD extract showed the presence of the dominant compound, -sitosterol, as determined by GC-MS analysis.